Prevalence of Eimeria oocysts in West African dwarf goat at the University of Ibadan farm (2002)
An outbreak of acute coccidiosis is reported in West African Dwarf (WAD) goats kept under semi- intensive management system at the University of Ibadan farm. During the period of the outbreak, clinical signs observed among the animal included anorexia, fever, coughing, ocular and nasal discharges and diarrhoea. Sixty nine out of eighty-five (85%) animals were scouring, 6 out of 20 (30%) pregnant does aborted, 8 out of 80 (10%) died through severe infection. Average oocyst counts was 2.73 x 10(5)/gram faeces in kids and 0.9 x 10(3)/gram faeces in adult goats. Eimeria species predominant in goats and percentage occurrence were E. arloingi (77.5%), E. ninakohlyakimovae (62.89%), E. hirci (58.6%). E. alijevi (39.5%). Areas of glandular degeneration and necrosis of epithelium of the small intenstine were seen. Also coccidia schizonts, immature oocysts, and neutrophilic infiltrations can be seen in the intestinal mucosa. The presence of pathogenic species of the Eimeria in WAD goats suggest that coccidiosis may be contributing to the enteric syndromes, poor feed conversion and low productivity.